Phytochemical and Mineral Composition of Triherbal Formulation - Umaru, Isaac John; Ejeh, Yakubu Ojochenemi; Shaibu, Isaac Eleojo; Onyindia, Agbo Christiana; Peter, Prosper Uneju; Sheneni, Victor Duniya (Darul Yasin Al Sys, 2025)
Herbal combinations are widely used for the treatment of various diseases in the developing countries. Their ability in boosting the immune system is a function of Mineral constituents present. Currently available drugs have been associated with number of side effects. Herbal Combinations have often been used in traditional medicine systems like Ayurveda, unani, African, Chinese Medicine, and Western herbalism. Combination of herbs is superior with increased therapeutic efficacy to individual herb. Triherbal combinations consisting of (Mucuna pruriens, Phyllantus amarus and Securidaca longipedunculata) 1:1:1 ratio W/W. The study was aimed at investigating the phytochemical profile, in-vivo antioxidant activities, The quantitative Phytochemical result revealed present of Alkaloids, Flavonoids, Terpenoids, Saponins and glycosides with Total phenol having the highest values (111.67±0.23mg/GAE/g) followed by (92.50±0.14mg/GAE/g). Chemical profiling analysis showed two prominent compounds chlorogenic acid (78.2 %) and Caffeic acid (21.8%.).The results of Mineral compositions clearly indicated that triherbal fromulation is a rich sources of minerals indicating the presence of the following: Sodium(Na), Potassium(k), Magnesium(Mg), Calcium(Ca), Iron(Fe), Phosphporus (P), and Zinc(Zn) with Magnesium having the highest value of (830.5±0.0) and the least value zinc (9.8±0.14). Conclusively, These findings indicate that these triherbal formulations contain the essential minerals and bioactive compounds consequently exhibiting diverse biochemical activities, through multiple mechanism that could probably boost the immune system, making this formulation a potential therapeutic interventions for preventing liver damage and maintaining overall health.